2015
DOI: 10.1260/0144-5987.33.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Analysis of Wind Power Resource Using Weibull Parameters

Abstract: In this study, wind data of eleven years (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) has been used to determine wind characteristics of Saudi Arabian city Jeddah. These characteristics include the daily, monthly and annual wind speed, wind probability density distribution, shape (k) and scale (c) parameters at 10 m height. The analysis revealed that yearly values of k ranged from 1.398 to 1.763 with a mean value of 1.590 and values of scale parameter c varied from 3.146 to 4.329 with mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Authors analyzed 100 turbines to select suitable turbines for chosen best sites at Yanbo, Dhahran, Dhulom, Riyadh, and Qaisumah in Saudi Arabia. Bassyouni et al (2015) used the wind data for a period of 11 years (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) to study the wind characteristics of Jeddah in Saudi Arabia. The results showed that maximum and minimum wind power potential was observed in the month of March and February.…”
Section: Introductionmentioning
confidence: 99%
“…Authors analyzed 100 turbines to select suitable turbines for chosen best sites at Yanbo, Dhahran, Dhulom, Riyadh, and Qaisumah in Saudi Arabia. Bassyouni et al (2015) used the wind data for a period of 11 years (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) to study the wind characteristics of Jeddah in Saudi Arabia. The results showed that maximum and minimum wind power potential was observed in the month of March and February.…”
Section: Introductionmentioning
confidence: 99%
“…Bassyouni et al [29] used Weibull distribution approach to analyze the wind power potential for Jeddah, the commercial capital of Saudi Arabia. The study concluded that under the present scenario, the wind power potential can be exploited for off-grid applications for power generation.…”
Section: Saudi Arabia's Wind Power Research and Development Updatementioning
confidence: 99%
“…Rehman et al [24] studied wind power potential of seven sites of Saudi Arabia and used Weibull function to study wind characteristics at three different heights. Bassyouni et al [25] analyzed the wind speed characteristics including daily, monthly, and annual wind speed, and wind probability density distribution, shape and scale parameters at 10-m height, based on 11 years wind data record of Jeddah city of Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%